Ocular injury during scaling: Are we protecting ourselves? - Anuradha Bhatsange; Japatti Sharanabasappa; Sabina Deshmukh; Siddhartha Varma (Wolters Kluwer Medknow Publications, 2016)
The risk of ocular injury in dentistry is mainly attributed to the use of power driven high speed Handpieces and ultrasonics. These ocular injuries may vary from mild irritation to grave implications such as blindness. Various studies have reported about such injuries and their consequences. The guidelines are laid by health associations regarding protective eyewear use during dental procedures. This study emphasizes about the need to protect the eye with protective eye wear, failing which a dental student suffered a serious ocular injury while performing manual scaling procedure.